The Body in Professional Practice, Learning and Education
XVI, 265 p. 9 illus.
Keywords: The body matters, in practice. How then might we think about the body in our work in and on professional practice, learning and education? What value is there in realising and articulating the notion of the professional practitioner as crucially embodied? Beyond that, what of conceiving of the professional practice field itself as a living corporate body? How is the body implicated in understanding and researching professional practice, learning and education? Body/Practice is an extensive volume dedicated to exploring these and related questions, philosophically and empirically. It constitutes a rare but much needed reframing of scholarship relating to professional practice and its relation with professional learning and professional education more generally. It takes bodies seriously, developing theoretical frameworks, offering detailed analyses from empirical studies, and opening up questions of representation. The book is organized into four parts: I. ‘Introducing the Body in Professional Practice, Learning and Education’; II. ‘Thinking with the Body in Professional Practice’; III. ‘The Body in Question in Health Professional Education and Practice’; IV. ‘Concluding Reflections’. It brings together researchers from a range of disciplinary and professional practice fields, including particular reference to Health and Education. Across fifteen chapters, the authors explore a broad range of issues and challenges with regard to corporeality, practice theory and philosophy, and professional education, providing an innovative, coherent and richly informed account of what it means to bring the body back in, with regard to professional education and beyond.